Reservoir properties and genesis of tight sandstones—A case study from the Gaotaizi oil layer in the Qijia area, Songliao basin - Si, Shanghua; Zhao, Yutao; Er, Chuang; Bai, Yubin; Wu, Weitao; He, Junhao (Frontiers in Earth Science, 2023)
The primary focus of oil and gas exploration for tight sandstone reservoirs is on a quantitative characterization of reservoir properties. This paper uses the tight sandstone reservoir developed in the Gaotaizi oil layer in the Qijia area of the Songliao Basin as an example. The petrology, physical properties, pore–throat characteristics, and the genesis of the densification of the oil-bearing sandstones are elucidated using casting thin-sections, scanning electron microscopy, 3D computerized tomography (CT), and petrophysical experimental techniques. The results show that the Gaotaizi oil layer is mainly composed of clastic rocks and contains small amounts of shell limestone. The clastic rocks are mainly lithic feldspar sandstone and feldspar lithic sandstone, while residual intergranular pores, intergranular dissolved pores, intragranular dissolved pores, intragranular pores and intercrystalline pores constitute the different pore types. Mercury intrusion and 3D CT analysis showed that micro-nano pores account for 53% of the total pores present. The pore–throat coordination number is distributed between 1 and 4, with an average of 1.8. The pores and throats in the Gaotaizi reservoir have poor connectivity. The porosity distribution of the Gaotaizi oil layer is 1.4–22.5%, with an average of 9.5%, while the permeability distribution ranges from 0.01 to 27.10 mD, with an average of 0.41 mD. It is an ultra-low porosity and ultra-low permeability tight reservoir. The Gaotaizi oil layer is divided into three types of reservoirs through a systematic study of its pore developmental characteristics. Diagenetic processes like compaction and cementation result in a reduction in porosity and permeability. Compaction, calcite and siliceous cementation, and illite packing are primarily responsible for reservoir densification.